STUDI PUSTAKA HUBUNGAN ETIKA PROFESI KEGURUAN DENGAN INTEGRITAS AKADEMIK GURU - Muhamad Imam Ghozali; Wina Alya Ramadhani; Muhammad Muhaimin; Nur Khasanah (Jurnal Pendidikan dan Ekonomi (JUPEK), 2026)
study is motivated by the importance of teachers’ professional ethics in strengthening teachers’ academic integrity amid the challenges of digital-era education and the development of Artificial Intelligence (AI). Low academic integrity, such as plagiarism, data manipulation, and misuse of technology, may reduce the quality of education and teachers’ professionalism. This study aims to describe the concept of teachers’ professional ethics, examine the nature of teachers’ academic integrity, analyze the relationship between the two, and identify efforts to strengthen professional ethics in developing an academic culture with integrity. The research employed a qualitative approach using a library research method through the review of books, scientific journal articles, and relevant previous studies. Data were analyzed using content analysis to systematically examine the main concepts. The findings reveal that teachers’ professional ethics are closely related to teachers’ academic integrity because professional ethics serve as a moral foundation in shaping honest, objective, disciplined, and responsible professional behavior. Furthermore, the development of digital technology and AI has created new challenges to academic integrity, making it necessary to strengthen professional ethics through training programs, implementation of ethical codes, improvement of digital literacy, and the establishment of a healthy academic culture. Therefore, strengthening teachers’ professional ethics is considered a strategic effort to create quality, humane, and integrity-based education.